AtSWEET1 negatively regulates plant susceptibility to root-knot nematode disease - Zhou, Yuan; Zhao, Dan; Duan, Yuxi; Chen, Lijie; Fan, Haiyan; Wang, Yuanyuan; Liu, Xiaoyu; Chen, Li-Qing; Xuan, Yuanhu; Zhu, Xiaofeng (Frontiers in Plant Science, 2023)
Abstract The root-knot nematode Meloidogyne incognita is a pathogenic pest that causes severe economic loss to agricultural production by forming a parasitic relationship with its hosts. During the development of M. incognita in the host plant roots, giant cells are formed as a nutrient sink. However, the roles of sugar transporters during the giant cells gain sugar from the plant cells are needed to improve. Meanwhile, the eventual function of sugars will eventually be exported transporters (SWEETs) in nematode-plant interactions remains unclear. In this study, the expression patterns of Arabidopsis thaliana SWEETs were examined by inoculation with M. incognita at 3 days post inoculation (dpi) (penetration stage) and 18 dpi (developing stage). We found that few AtSWEETs responded sensitively to M. incognita inoculation, with the highest induction of AtSWEET1, a glucose transporter gene. Histological analyses indicated that the β-glucuronidase (GUS) and green fluorescent protein (GFP) signals were observed specifically in the galls of AtSWEET1-GUS and AtSWEET1-GFP transgenic plant roots, suggesting that AtSWEET1 was induced specifically in the galls. Genetic studies have shown that parasitism of M. incognita was significantly affected in atsweet1 compared to wild-type and complementation plants. In addition, parasitism of M. incognita was significantly affected in atsweet10 but not in atsweet13 and atsweet14, expression of which was induced by inoculation with M. incognita. Taken together, these data prove that SWEETs play important roles in plant and nematode interactions.